1989
DOI: 10.1002/1097-4679(198907)45:4<651::aid-jclp2270450423>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Pattern analysis of Wechsler Intelligence Scale for Children-Revised profiles of delinquent boys

Abstract: To help meet the prescriptive needs of juvenile delinquents more effectively, an analysis of the Wechsler Intelligence Scale for Children‐Revised (WISC‐R), utilizing Lutey's model of Factor Analytic measures, was performed on 82 profiles obtained from male subjects (aged 13‐16) in a Wisconsin correctional facility. Results support the trends of previous studies of juvenile delinquency; a significant 70% of the subjects (χ2 6.4, p <.05) had a higher Performance than Verbal score (M = 13.2). The Performance‐Verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…). In addition, many studies report relatively greater deficits on Verbal IQ (VIQ) than on Performance IQ (PIQ), often referred to as a PIQ > VIQ discrepancy (Culberton, Feral, & Gabby, 1989; Haynes & Bensch, 1981; Hays, Solway, & Schreiner, 1978; Hecht & Jurkovic, 1978; Hubble & Groff, 1981; Ollendick, 1979). Several reviewers conclude that IQ is one of the most important predictors of delinquency, so that it is critical to understand the link between intellectual deficits and the development of delinquent behavior (Hirshi & Hindelang, 1977;Quay, 1987; Wilson & Herrnstein, 1985).…”
Section: ;mentioning
confidence: 99%
“…). In addition, many studies report relatively greater deficits on Verbal IQ (VIQ) than on Performance IQ (PIQ), often referred to as a PIQ > VIQ discrepancy (Culberton, Feral, & Gabby, 1989; Haynes & Bensch, 1981; Hays, Solway, & Schreiner, 1978; Hecht & Jurkovic, 1978; Hubble & Groff, 1981; Ollendick, 1979). Several reviewers conclude that IQ is one of the most important predictors of delinquency, so that it is critical to understand the link between intellectual deficits and the development of delinquent behavior (Hirshi & Hindelang, 1977;Quay, 1987; Wilson & Herrnstein, 1985).…”
Section: ;mentioning
confidence: 99%
“…Otizm, DSM-IV-TR ("Diagnostic and Statistical Manual of Mental Disorders 4th edition text revision") tanı ölçütlerine göre tanılandırıldı (11). Zeka düzeyleri için 6-16 yaş arasındaki çocuklara Wechsler çocuklar için zekâ ölçeği (WISC-R) uygulandı (12,13). Toplam zeka puanı 70 üzeri normal zeka düzeyi olarak değerlendirildi.…”
Section: Introductionunclassified
“…(2016) found considerable evidence that young people in contact with the criminal justice system perform poorly on language measures relative to their peers. Other studies have also demonstrated that these youth exhibit poorer verbal intelligence quotient scores than performance intelligence quotient scores on Wechsler scales, signifying an explicit deficit in cognitive skills associated with language (Cornell & Wilson, 1992; Culberton et al., 1989; Romi & Marom, 2007).…”
Section: Introductionmentioning
confidence: 97%